Plasma prednisolone levels from enteric and non-enteric coated tablets estimated by an original technique. - Morrison, P J (1977)
1 A quantitative thin layer chromatographic technique for the estimation of plasma prednisolone levels has been devised with a minimum level of estimation of 10 ng/ml. 2 A comparative study of the absorption of 5 and 10 mg prednisolone from enteric and non-enteric coated tablets (5 mg) was carried out in healthy subjects. 3 Mean plasma half-life and peak plasma concentrations obtained from the non-enteric coated preparation agree well with previous studies in normal subjects reported by other investigators using competitive protein binding or radioimmunoassay techniques. Intersubject variability in bioavailability was noted. 4 Enteric coating increased the lag time before prednisolone appeared in the blood but did not alter the bioavailability of prednisolone compared to the equivalent dose of the non-enteric coated tablet.